2017
DOI: 10.21577/0103-5053.20170237
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube-Supported Copper-Cobalt Catalyst for the Production of Higher Carbon Number Alcohols through Carbon Monoxide Hydrogenation

Abstract: A series of carbon nanotube (CNTs)-supported copper-cobalt catalysts were prepared and investigated in a slurry reactor for their ability to selectively convert syngas into higher carbon number alcohols. The 7.5Cu7.5Co/CNTs catalyst achieved superior selectivity towards the formation of ethanol (30.1%) and C 2+ alcohols (57.7%), while the 10Co5Cu/CNTs catalyst exhibited the largest alcohol space-time yield (372.9 mg g cat -1 h -1). However, the pure Cu (15Cu/CNTs) catalyst displayed negligible activity. Cobalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…3 c), displays two peaks of Cu 2p 3/2 and Cu 2p 1/2 which are decomposed into two peaks at 937.16 and 952.72 eV, corresponding to Cu 0 with satellite peaks appeared at higher binding energy, indicating the existence of Cu 2+ . The ratio of Cu 0 and Cu 2+ has been calculated 95:5 respectively 48 .
Figure 3 X-ray photoelectron spectroscopy survey analysis ( a ) and the high-resolution spectra of Zn 2p and Cu 2p ( b ), ( c ) respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…3 c), displays two peaks of Cu 2p 3/2 and Cu 2p 1/2 which are decomposed into two peaks at 937.16 and 952.72 eV, corresponding to Cu 0 with satellite peaks appeared at higher binding energy, indicating the existence of Cu 2+ . The ratio of Cu 0 and Cu 2+ has been calculated 95:5 respectively 48 .
Figure 3 X-ray photoelectron spectroscopy survey analysis ( a ) and the high-resolution spectra of Zn 2p and Cu 2p ( b ), ( c ) respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…Dovnar R et al [19] researched the antibacterial ability of Cu and Se, and found that Cu have significant effects on Gram positive and Gram negative microorganisms. Alloys composed of Cu and Co atoms have more unique properties and applications, such as catalytic properties [20][21][22], magnetic properties [23], and energy storage characteristics [24], etc. Therefore, it is of great interest to analyze the growth process of Co on Cu substrates.…”
Section: Introductionmentioning
confidence: 99%